1997
DOI: 10.1111/j.1365-2915.1997.tb00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Isozymic and metric variation in the Lutzomyia longipalpis complex

Abstract: Male Lutzomyia longipalpis of two types from Bolivia were compared using isozyme electrophoresis and wing morphometry. One sample (ex Chiflonkaka Cave, alt. 2800 m at Toro Toro, Charcas Province, Potosi Department) was 'two-spot' phenotype males (i.e. tergites III and IV with paired pale patches of pheromone glands), whereas two other locality samples (Apa Apa and Imanaco, Sud Yungas Province, La Paz Department) were one-spot male phenotype (only tergite IV with paired pale patches). Multilocus enzyme electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 23 publications
(19 reference statements)
1
40
1
5
Order By: Relevance
“…Colonies of L. longipalpis have been successfully established before (Sherlock & Sherlock 1959, Killick-Kendrick et al 1977, Ready 1978,1979, Modi & Tesh 1983, Buescher et al 1984. L. longipalpis populations from Central and South America show a great polymorphism in behavior, morphology and biochemical characters (Ward et al 1983, Hamilton et al 1996, Dujardin et al 1997, Mukhopadhyay et al 1998a, b, Dias et al 1998, Yin et al 1999. These results either lead L. longipalpis differences to be suspected as due to a complex of cryptic species (Lanzaro et al 1993, Warburg et al 1994 This work was partially supported by Capes (MSc scholarship to JFLM) and by the State Government of Roraima.…”
Section: Methodsmentioning
confidence: 99%
“…Colonies of L. longipalpis have been successfully established before (Sherlock & Sherlock 1959, Killick-Kendrick et al 1977, Ready 1978,1979, Modi & Tesh 1983, Buescher et al 1984. L. longipalpis populations from Central and South America show a great polymorphism in behavior, morphology and biochemical characters (Ward et al 1983, Hamilton et al 1996, Dujardin et al 1997, Mukhopadhyay et al 1998a, b, Dias et al 1998, Yin et al 1999. These results either lead L. longipalpis differences to be suspected as due to a complex of cryptic species (Lanzaro et al 1993, Warburg et al 1994 This work was partially supported by Capes (MSc scholarship to JFLM) and by the State Government of Roraima.…”
Section: Methodsmentioning
confidence: 99%
“…Further evidence for the presence of cryptic species within a Lu. longipalpis complex has been provided by numerous other workers (Dujardin et al 1997, Lampo et al 1999, Uribe, 1999, Yin et al 1999, Arrivillaga & Feliciangeli 2001, Soto et al 2001, Arrivillaga et al 2002.…”
Section: Lu Longipalpis: the Major Vector Of Avlmentioning
confidence: 99%
“…However, additional studies failed to corroborate these findings and showed that fertile crosses could occur between populations characterized as having the one-spot and the two-spot phenotypes (Ward et al 1988). Recent work by Dujardin et al (1997) indicates that the "two spot phenotype" also occurs in Paraguay and Bolivia and that the pale patch character cannot be related to transmission efficiency. Also Mukhopadhyay et al (1998a) using isozymes to study populations from Brazil, determined that the spot phenotype appears to be a polymorphic character not related to genetic isolation or differentiation at the species level.…”
Section: Morphological Variabilitymentioning
confidence: 99%
“…The influence of colonization on genetic structure, and how this may relate to comparisons made between laboratory colonies, has been the subject of considerable discussion (Lanzaro et al 1993, Munsterman 1994, Lanzaro & Warburg 1995, Dujardin 1997. Mukhopadhyay et al (1997) compared the genetic profiles of 14 loci in five colonies of Lu.…”
Section: Isozymic Variabilitymentioning
confidence: 99%
See 1 more Smart Citation